Rancang Bangun Mesin Pencetak Pelet Ikan Multifungsi - Rahmat Fajrul; Akmal Indra; Bambang Dwi Haripriadi (Jurnal INOVATOR, 2023)
One of the obstacles in raising tapah fish is in the supply of feed. Tapah fish is a carnivorous predatory fish that eats small fish so it is very dependent on live fish feed. For this reason, it is necessary to get used to feeding with artificial feed (pellets). Usually for one time the process of making feed uses a total weight of 10 kg of raw materials and takes approximately 4 hours. This situation is very detrimental to fish farmers because they cannot increase the number of fish and the number of ponds anymore due to limited feed in the form of pellets. Apart from raising tapah fish, the people of Lubuk Gaung Village also have a poultry business, especially chicken livestock. The feed used in this poultry is milled corn feed. In the manufacture of ground corn feed, 60% is corn raw material. Corn grain size is very influential on the growth of poultry. Both of these machines are already sold on the market separately, it's just that these two machines are quite expensive. For animal feed pellet machines, they are sold at a price of Rp. 15,760,000 and a corn grinding machine is sold at Rp. 8,500,000